Catalytic performance of non-alloyed bimetallic PtAu electrocatalysts for methanol oxidation reaction. (21st December 2017) - Feng, Yuan-Yuan; Song, Gui-Hua; Zhang, Qiang; Hu, Hua-Shuai; Feng, Mei-Ying; Wang, Jing-Yi; Kong, De-Sheng
Abstract: Reduced graphene oxide (RGO) supported Pt m Au electrocatalysts with different atomic Pt/Au ratios ( m = 0.5–2.0) are prepared via co-reduction of H2 PtCl6 and HAuCl4 . The catalysts are comprehensively characterized through TEM, XRD and XPS. The catalytic behaviors of the Pt m Au catalysts toward methanol oxidation reaction (MOR) in alkaline electrolyte are investigated via cyclic voltammetry (CV) and chronoamperometry (CA) techniques. Results show that methanol oxidation currents on the Pt m Au catalysts are higher than that on pure Pt catalyst, suggesting that the introduction of Au in Pt catalyst can significantly promote the catalytic properties of Pt. Among the Pt m Au catalysts, Pt1.0 Au/RGO shows the highest mass-specific activity (MSA) and intrinsic activity (IA). The MSA and IA of Pt1.0 Au/RGO is 0.72 A mg −1 Pt+Au and 105.4 A m −2 Pt, which are ca . 2.40 and 3.56 times those of Pt/RGO (0.30 A mg −1 Pt+Au and 29.6 A m −2 Pt ), respectively. CO stripping voltammograms and CV curves suggest that the improved electrocatalytic properties of the Pt m Au/RGO catalysts are especially attributed to the decreased CO formation rather than the facile removal of CO on the surface of Pt. The findings of this work have potential applications in understanding the mechanism of MOR and designing highly effective Pt-based anodic catalysts of direct methanol fuel cells. Highlights: Reduced graphene oxide supported bimetallic Pt m Au electrocatalysts are prepared. The catalytic properties for methanol oxidation reaction (MOR) are investigated. The introduction of Au exhibits significant promoting effect to Pt for MOR. Decreased CO formation on Pt is the key reason for the enhanced catalytic activity.